2018
DOI: 10.2460/ajvr.79.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ADAMTS17 in Chinese Shar-Pei with primary open-angle glaucoma, primary lens luxation, or both

Abstract: OBJECTIVE To evaluate the coding regions of ADAMTS17 for potential mutations in Chinese Shar-Pei with a diagnosis of primary open-angle glaucoma (POAG), primary lens luxation (PLL), or both. ANIMALS 63 Shar-Pei and 96 dogs of other breeds. PROCEDURES ADAMTS17 exon resequencing was performed on buccal mucosal DNA from 10 Shar-Pei with a diagnosis of POAG, PLL, or both (affected dogs). A candidate causal variant sequence was identified, and additional dogs (53 Shar-Pei [11 affected and 42 unaffected] and 95 dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Indeed, the word “basset” comes from the medieval French for “of low stature” [22]. It could therefore be speculated, given that five different ADAMTS17 mutations have now been identified in breeds of small stature [35, 13], that this locus could be under positive selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the word “basset” comes from the medieval French for “of low stature” [22]. It could therefore be speculated, given that five different ADAMTS17 mutations have now been identified in breeds of small stature [35, 13], that this locus could be under positive selection.…”
Section: Discussionmentioning
confidence: 99%
“…A different mutation in ADAMTS17 (a deletion of six base pairs on canine chromosome 3 at co-ordinates 40,935,387 – 40,935,393 (CanFam 3.1) has more recently been identified in the Shar Pei (SP) [5]. As in the PBGV, this mutation causes an autosomal recessive form of POAG, and primary lens luxation (PLL) is also associated with this mutation [5, 11]. An independent ADAMTS17 mutation has been shown to cause PLL in several breeds [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…As veterinary ophthalmologists we have a unique opportunity to study how the biomechanical properties of the ocular tissues affect susceptibility to IOP. For example, we observe that ADAMTS10 ‐mutant beagles and ADAMTS17 ‐mutant Chinese shar‐peis with POAG maintain eye sight longer with slower progression of ONH atrophy than many other glaucomatous dog breeds with comparable pressures . While proof still needs to be provided that tissue properties are linked to IOP susceptibility in dogs, initial biomechanical studies in ADAMTS10 ‐mutant beagles showed that their posterior sclera is weaker with reduced fibrous collagen density .…”
Section: Novel Treatment Strategies For the Futurementioning
confidence: 92%
“…However, most mutations are located in the domains comprising the catalytic domain and there is a notable paucity of mutations located in the ancillary domains. Mutations in ADAMTS17 are also associated with short stature, lens dislocation, and glaucoma in several dog breeds, suggesting a fundamental role for ADAMTS17 in bone growth and in the formation and/or homeostasis of the ciliary zonule which is comprised of fibrillin microfibrils and holds the lens in place [43][44][45][46][47]. ADAMTS10 and ADAMTS17 were identified in a genome-wide association study (GWAS) of more than 12,000 cases versus 390,000 controls as susceptibility loci likely to cause carpal tunnel syndrome [48].…”
Section: Disorders Associated With Mutations In Adamts6 10 17 and 19mentioning
confidence: 99%